THE IMPACT OF FEATURE SELECTION: A DATA‐MINING APPLICATION IN DIRECT MARKETING. Issue 1 (5th March 2013) - Tan, Ding‐Wen; Yeoh, William; Boo, Yee Ling; Liew, Soung‐Yue
SUMMARY The capability of identifying customers who are more likely to respond to a product is an important issue in direct marketing. This paper investigates the impact of feature selection on predictive models which predict reordering demand of small and medium‐sized enterprise customers in a large online job‐advertising company. Three well‐known feature subset selection techniques in data mining, namely correlation‐based feature selection (CFS), subset consistency (SC) and symmetrical uncertainty (SU), are applied in this study. The results show that the predictive models using SU outperform those without feature selection and those with the CFS and SC feature subset evaluators. This study has examined and demonstrated the significance of applying the feature‐selection approach to enhance the accuracy of predictive modelling in a direct‐marketing context. Copyright © 2013 John Wiley & Sons, Ltd.